2008
DOI: 10.1007/s00421-008-0809-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of milk and a carbohydrate-electrolyte drink on the restoration of fluid balance and exercise capacity in a hot, humid environment

Abstract: Following a 2.0 +/- 0.1% body mass loss induced by intermittent exercise in the heat, seven male volunteers ingested either a carbohydrate-electrolyte solution (CE) or skimmed milk (M) in a volume equal to 150% of body mass loss. At the end of the 3 h recovery period, subjects were essentially in positive fluid balance on trial M (191 +/- 162 mL), and euhydrated on trial CE (-135 +/- 392 mL) despite being in negative sodium balance on both trials and negative potassium balance on trial CE. This difference of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 30 publications
7
82
3
Order By: Relevance
“…Both Seifert et al (2006) and Watson et al (2008) observed that plasma/ serum osmolality was greater after ingestion of a drink containing protein. Whilst there was no significant difference in serum osmolality between the W and WP trials in the present study, there was a tendency for a main effect of trial (P=0.062) and mean values were higher in the 3 h after drinking during WP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Seifert et al (2006) and Watson et al (2008) observed that plasma/ serum osmolality was greater after ingestion of a drink containing protein. Whilst there was no significant difference in serum osmolality between the W and WP trials in the present study, there was a tendency for a main effect of trial (P=0.062) and mean values were higher in the 3 h after drinking during WP.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, little is known about the effects of protein on post-exercise rehydration. Shirreffs et al (2007b) demonstrated that after exercise-induced dehydration, ingestion of skimmed milk resulted in greater drink retention than when a traditional carbohydrate-electrolyte sports drink was ingested, a finding confirmed by Watson et al (2008). There are a number of compositional differences between skimmed milk and a carbohydrate-electrolyte sports drink (i.e.…”
Section: Introductionmentioning
confidence: 87%
“…In adults, much of the focus in recent years has shifted toward the use of bovine-based milk and milk products as potential postexercise beverages (12,17,18,25), however, very little is known about how this research translates to the pediatric population. Although the combined effects of milk (more specifically, calcium) and exercise have been recognized in the promotion of optimal bone development in children (6,20), the protein needs of this population are not well understood because they remain relatively understudied.…”
mentioning
confidence: 99%
“…It was reported that the plasma volume after the administration of skim milk showed a change similar to that of a carbohydrateelectrolyte drink with an almost identical composition to that of a sports drink (Watson et al, 2008). Casein and whey protein in skim milk are digested and absorbed as peptides or amino acids.…”
Section: Discussionmentioning
confidence: 97%